Research on the Flexural Performance of Shield Tunnel Segments Strengthened with Fabric-Reinforced Cementitious Matrix Composite Panels - Caixia Guo; Kaiwen Yang; Yichen Duan; Jiulin Li; Jianlin Wang; Weidong Lu (Buildings)
To investigate the strengthening effectiveness of Fabric-Reinforced Cementitious Matrix (FRCM) composites on shield tunnel segments, this study conducted four-point bending tests on FRCM composite panels. The influence of different cementitious matrices (engineered cementitious composite, ECC; ultra-high-performance concrete, UHPC) on the flexural behavior of FRCM panels was systematically analyzed. Numerical simulations were additionally conducted to analyze deformation behavior, damage progression, and stress variations in steel reinforcements within standard structural segments strengthened with FRCM composite panels. A parametric analysis was performed to assess the effects of cementitious matrix type, panel thickness, and carbon fiber-reinforced polymer (CFRP) grid layers on the reinforcement efficiency. The experimental results demonstrated that FRCM composite panels exhibit superior flexural performance. Specimens with UHPC matrices exhibited higher cracking stresses and enhanced flexural stiffness during the elastic phase, while those with ECC matrices demonstrated advantages in post-peak hardening behavior and energy dissipation capacity. Both matrix types achieved similar cracking strains and comparable ultimate flexural strengths. Numerical simulations revealed that FRCM strengthening significantly improves the ultimate flexural bearing capacity of segments while effectively controlling deformation. For UHPC-based FRCM reinforced segments, the ultimate bearing capacity increased with both UHPC thickness and CFRP layer quantity. In contrast, ECC-based FRCM reinforced segments exhibited capacity enhancement primarily correlated with CFRP layer addition, with negligible sensitivity to ECC thickness variations.